Food fraud in selected sub-Saharan Africa countries: a wake-up call to national regulatory bodies to support enforcement and food safety - Njiru, Joshua M.; Njeru, Evalyne; Kang’iri, Jacqueline; Lunani, Isabella; Rotich, Henry; Muriira, Geoffrey; Tombito, Collins; Nyaboga, Evans N. (Frontiers in Food Science and Technology, 2025)
Africa is projected to have 2.4 billion people by 2050 and provision of healthy and nutritious diets is one of the challenges facing food systems. Food fraud is an act of deliberate adulteration and counterfeiting of food ingredients and commodities at all stages of supply chains with the aim of economic gain. Food fraud in Africa is a menace both in public health and for the economic development. Food fraud is perpetuated at all stages of the food supply chain to alter the quality of food products for economic gain or financial advantage thus threatening food safety. In addition, limited information is available on food fraud monitoring/manifestation in Africa thus hindering the prevention efforts. The standard bodies in sub-Saharan Africa countries play a vital role in combating food fraud. However, weak reporting mechanisms and regulatory systems in Africa remains a challenge in controlling food fraud. This current review explores food fraud in Africa and stakeholder (consumers, industries and regulators) challenges in the supply chain in attempt to combat food fraud. The recommendations of the review will be helpful to policymakers and scientists in improving the quality and safety of food along the supply chain, and in reducing fraud. Quality testing infrastructure and technical know-how are very important for frequent and rigorous quality control of food products and food fraud prevention. The standard and regulatory bodies in African governments need to strengthen and comply with the regulations that govern food fraud and support enforcement and food safety.